Positional Enrichment by Proton Analysis (PEPA): A One‐Dimensional 1H‐NMR Approach for 13C Stable Isotope Tracer Studies in Metabolomics. (21st February 2017) - Vinaixa, Maria; Rodríguez, Miguel A.; Aivio, Suvi; Capellades, Jordi; Gómez, Josep; Canyellas, Nicolau; Stracker, Travis H.; Yanes, Oscar
Abstract: A novel metabolomics approach for NMR‐based stable isotope tracer studies called PEPA is presented, and its performance validated using human cancer cells. PEPA detects the position of carbon label in isotopically enriched metabolites and quantifies fractional enrichment by indirect determination of 13 C‐satellite peaks using 1D‐ 1 H‐NMR spectra. In comparison with 13 C‐NMR, TOCSY and HSQC, PEPA improves sensitivity, accelerates the elucidation of 13 C positions in labeled metabolites and the quantification of the percentage of stable isotope enrichment. Altogether, PEPA provides a novel framework for extending the high‐throughput of 1 H‐NMR metabolic profiling to stable isotope tracing in metabolomics, facilitating and complementing the information derived from 2D‐NMR experiments and expanding the range of isotopically enriched metabolites detected in cellular extracts. Abstract : PEPA ist eine neuartige Methode, die das metabolische Hochdurchsatz‐1D‐ 1 H‐NMR‐Profiling auf die Detektion stabiler 13 C‐Isotope erweitert. Der Ansatz vergrößert das Spektrum detektierbarer isotopenangereicherter Metabolite in zellulären Extrakten und forciert damit die Implementierung der NMR‐Spektroskopie in Zellmetabolismusstudien.